2014
DOI: 10.1002/2014ja019900
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protons reflected by lunar crustal magnetic fields on the global lunar plasma environment

Abstract: Solar wind plasma interaction with lunar crustal magnetic fields is different than that of magnetized bodies like the Earth. Lunar crustal fields are, for typical solar wind conditions, not strong enough to form a (bow)shock upstream but rather deflect and perturb plasma and fields. Here we study the global effects of protons reflected from lunar crustal magnetic fields on the lunar plasma environment when the Moon is in the unperturbed solar wind. We employ a three‐dimensional hybrid model of plasma and an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 52 publications
(103 reference statements)
6
43
0
Order By: Relevance
“…Thus, ARTEMIS observations suggest an interaction driven by the reflected protons from crustal magnetic fields rather than by the magnetic fields themselves, consistent with Fatemi et al [2014].…”
Section: 1002/2014gl061973supporting
confidence: 77%
See 4 more Smart Citations
“…Thus, ARTEMIS observations suggest an interaction driven by the reflected protons from crustal magnetic fields rather than by the magnetic fields themselves, consistent with Fatemi et al [2014].…”
Section: 1002/2014gl061973supporting
confidence: 77%
“…We note that simulation results [Fatemi et al, 2014] show the greatest solar wind flow deflection and enhancement in density and magnetic field in the hemisphere where the convection electric field points into the surface. In support of this, we have found that most events with shock-like features seen by ARTEMIS occur for a similar geometry (not shown).…”
Section: 1002/2014gl061973mentioning
confidence: 73%
See 3 more Smart Citations